BIOPROSPECT OF BACTERIAL FIBRINOLYTIC PROTEASE FROM BEKASAM OF LONGTAIL TUNA AS ANTITHROMBOTIC AGENT: LITERATURE REVIEW AND BIBLIOGRAPHY STUDY - Trianes, Juwy; Ethica, Stalis N.; Afriansyah, M. Ardi; Darmawati, Sri; Rahmani, Nanik; Zilda, Dewi S. (Politeknik Kesehatan Kemenkes RI Jakarta I, 2024)
Introduction:Cardiovascular disease (CVD) is the leading cause of death worldwide, with thrombosis being a significant risk factor. Fibrinolytic proteases have potential as antithrombotic agents and could be developed into CVD drugs. Indonesia's traditional fermented products, such as fish Bekasam, are rich in microorganisms, including fibrinolytic protease-producing bacteria, yet their potential for CVD treatment is underexplored. Fish paste in Indonesia serves as a protein source and a reservoir of bacterial diversity, which could aid in discovering new antithrombotic agents. Objective: This literature review examines research trends over the past decade on fibrinolytic protease-producing bacteria in traditional fermented products, with a focus on Bekasam made from Longtail Tuna. This fermented food is an alternative source for obtaining bacteria with antithrombotic properties. Methods: Data for this review were sourced from Google Scholar, PubMed, and the dimension.ai database, using the keyword